Can Elevated Pretreatment Serum Carcinoembryonic Antigen Levels Serve as a Potential Biomarker Guiding Adjuvant Chemotherapy in Rectal Cancer Patients With ypTis-3N0 After Neoadjuvant Radiotherapy and Surgery? - Huang, Chi; Jiang, Mingkun; Li, Yan; Tang, Chaoyang; Ma, Xiang; Huan, Xiangkun (Frontiers in Oncology, 2021)
Survival benefit of adjuvant chemotherapy (ACT) remained controversial in patients with stage II/III rectal cancer (RC) who received neoadjuvant therapy and surgery. This study was to investigate guiding role of elevated pretreatment serum carcinoembryonic antigen (CEA) levels for receiving ACT in yield pathological Tis-3N0 (ypTis-3N0) RC patients after neoadjuvant radiotherapy and surgery. Between 2004 and 2015, 10973 RC patients with ypTis-3N0 who received neoadjuvant radiotherapy and radical surgery were retrospectively analyzed using the Surveillance, Epidemiology, and End Results (SEER) database. Compared with CEA-normal group, elevated-CEA patients had worse 5-year CSS rate (90.1% vs 83.5%). 5-year CSS rate were 86.3% and 87.4% for ypTis-3N0M0 patients with or without ACT. Patients receiving ACT had a comparable 5-year CSS rate compared to those who did not regardless of CEA levels in ypTis-3N0M0 RC patients (CEA elevation group: 76.4% vs 83.5%, P=0.305; CEA normal group: 90.0% vs 90.1%, P=0.943). Intriguingly, ypT3N0M0 RC patients with elevated CEA levels may benefit from ACT (5-year CSS: 69.1% vs 82.9%, P=0.045), while those with normal CEA levels did not (5-year CSS: 89.3% vs 89.3%, P=0.885). Multivariate Cox analysis demonstrated that ACT tended to be a protective factor in elevated-CEA ypT3N0M0 RC patients (HR=0.633, 95% CI=0.344-1.164, P=0.141), while ACT was not associated with improved CSS in normal-CEA ypT3N0M0 RC patients (HR=1.035, 95% CI=0.487-2.202, P=0.928). Elevated pretreatment serum CEA levels may serve as a promising biomarker guiding ACT in rectal cancer patients with ypT3N0M0.